The effect of adding red spinach leaf extract (Amaranthus tricolor) with different concentrations on the quality of chicken meatballs - Ika Rezvani Aprita; Mulla Kemalawaty; Chairil Anwar; Irhami; Suri Purnama Febri; Suraiya Nazlia (Fakultas Pertanian Universitas Samudra, 2023)
Meatballs are one of the processed food products made from meat and have a fairly high composition of protein, minerals, and vitamins. Red spinach (Amaranthus Tricolor) is one of the vegetables that is less popular among the public. Red spinach contains high antioxidants. This study aims to determine the amount and effect of adding red spinach leaf extract on the quality of chicken meatballs produced. The experimental design used in this study was a complete randomized design (RAL) with a red spinach extract concentration factor consisting of 4 treatment levels, namely A = 0%, B = 10%, C = 30%, D = 50%. Each treatment was carried out 5 times so that 20 experimental units were obtained. The results showed that the addition of red spinach leaf extract with different concentrations of 0%, 10%, 20%, and 50% had a significant effect on the color, taste, aroma, and texture of the resulting chicken meatballs. The best treatment obtained is treatment B where the concentration of adding spinach leaf extract as much as 10% to chicken meatballs according to sensory analysis